Lessons for the Implementability and Sustainability of the SURG-Africa Model of Malawi in Colombia; Comment on “Improving Access to Surgery Through Surgical Team Mentoring – Policy Lessons From Group Model Building With Local Stakeholders in Malawi” - Jaime Hernán Rodríguez Moreno; Jesús Velandia; Diana Igua (International Journal of Health Policy and Management, 2022)
The development of models that allow improving the quality to achieve person-centered care is a challenge for any health system, especially in low- and middle-income countries, due to the economic difficulties inherent to the countries and to the cost involved in its implementation, which should be assumed by the states, avoiding that the economic burden is assumed by the population, and approaching the goal of universal health coverage. The availability of human talent and efficiency in the use of basic and specialized human talent is a necessity to improve safe access to health services, in this sense, the model proposed by SURG-Africa and whose sustainability in Malawi was evaluated, is an important reference for the establishment and sustainability of these models with other specialties and in other countries. Through this article, the elements of education, care model and financing for the implementation of the strategy in family medicine in the Colombian health system are explored.